Highly-Distributed Sensor Processing using IoT for Critical Infrastructure Monitoring - Babazadeh,M; Kartakis,S; McCann,JA (IEEE, 2018)
Highly-distributed signal processing for critical monitoring infrastructures has been a main research topic over the last decade. Under this context, we show the three phases of the joint "Cyber-physical control system" project; a collaboration between Imperial College London and NEC Corp. Japan. First, the implementation of edge processing with multiple tasks including data mining and communication, developed on a lightweight single core low-powered MCU system is presented. This algorithm has been effectively customized to be implemented on resource-constrained embedded systems. The developed sensor network is coupled with a low-powered wide range LoRa platform for transmission of the minimized payload. The work explores the node-to-node communication limitations and discusses how edge processing can be used for water network control and we present the overview of a Cyber-physical control system which is concerned with the event-triggered control of a water network. Finally, the results of the LoRa communication tests are given.